Loose parts 3 : inspiring culturally sustainable environments - Daly, Lisa; Beloglovsky, Miriam (Redleaf Press, 2018)
"Loose Parts 3 contains inspiration and guidance on how to create early childhood environments that are culturally sensitive. Authors Lisa Daly and Miriam Beloglovsky gathered a multicultural advisory board to help identify opportunities to promote cultural sustainability while avoiding generalization and bias."--Page [4] of cover.